Complete Genome Sequence Analysis of Ralstonia solanacearum Strain PeaFJ1 Provides Insights Into Its Strong Virulence in Peanut Plants - Tan, Xiaodan; Dai, Xiaoqiu; Chen, Ting; Wu, Yushuang; Yang, Dong; Zheng, Yixiong; Chen, Huilan; Wan, Xiaorong; Yang, Yong (Frontiers in Microbiology, 2022)
Bacterial wilt of peanut (Arachis hypogaea L.) caused by Ralstonia solanacearum is a devastating soil-borne disease which seriously restricted the world peanut production. However, the molecular mechanism of R. solanacearum-peanut interaction remains largely unknown. We found that R. solanacearum HA4-1 and PeaFJ1 isolated from peanut plants showed different pathogenicity by inoculating more than 110 cultivated peanuts. Phylogenetic tree analysis demonstrated that HA4-1 and PeaFJ1 both belonged to phylotype I and sequevar 14M, which indicating a high degree of genomic homology between them. Genomic sequencing and comparative genomic analysis of PeaFJ1 revealed 153 strain specific genes compared with HA4-1. The PeaFJ1 strain specific genes consisted of diverse virulence-related genes including LysR-type transcriptional regulators, two-component systems related genes and genes contributing to motility and adhesion. In addition, the repertoire of the type III effectors of PeaFJ1 was bioinformatically compared with that of HA4-1 to find the candidate effectors responsible for their different virulence. There are 79 effectors in PeaFJ1 genome, only 4 of which are different effectors compared with HA4-1, including RipS4, RipBB, RipBS and RS_T3E_Hyp6. Based on the virulence profiles of the two strains against peanuts, we speculate that RipS4 and RipBB are candidate virulence effectors in PeaFJ1 while RipBS and RS_T3E_Hyp6 are avirulence effectors in HA4-1. In general, our research greatly reduced the scope of virulence-related genes and made it easier to find out the candidates that caused the difference in pathogenicity between the two strains. These results will help to reveal the molecular mechanism of peanut-R. solanacearum interaction and develop targeted control strategies in the future.